Re-examining the Influence of the Old Testament Background on Joseph's Fatherhood in Mathew 1:18-20 - Sachia Ikyernum; Silas Gudamishi; Jonathan Oraduen Tarter (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study re-examines the influence of the Old Testament background on the portrayal of Joseph’s fatherhood in Matthew 1:18–20. Addressing gaps in prior scholarship that treats legal or theological aspects separately, this article integrates Jewish conceptions of righteousness, law, and familial duty to explain Joseph’s actions. Through grammatico-historical exegesis, the study shows that Mary’s pregnancy during betrothal constituted a serious legal violation. Joseph’s intention to divorce her quietly reflects his identity as dikaios, balancing Torah justice (mishpat) and compassion (chesed). The analysis further argues that divine revelation transforms Joseph’s righteousness, leading him beyond legal compliance to obedient faith. By accepting Jesus as his legal son, Joseph fulfills Old Testament ideals of Davidic lineage and responsible fatherhood. Consequently, Joseph’s fatherhood exemplifies a transition from legal piety to faithful discipleship, offering ethical implications for parenting and church teaching.